Effect of Photograph-Capturing Devices on The Anthropometric Analysis of Maxillary Incisor Display - Indrani Sulistyowati; Annisaa Putri Ariyani; Wita Anggraini; Syifa Sistasia; Keniyawati Keniyawati; Harris Gadih Pratomo (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2026)
An aesthetic smile enhances a person's attractiveness and has a positive impact on psychosocial health. The maxillary incisor display takes an important role in achieving an aesthetic smile. Therefore, dentists must ensure that their treatments do not interfere with the appearance of these teeth. Anthropometric analysis of maxillary incisor display is generally performed using profile photographs while smiling, taken with a digital camera. However, due to the limitation of face-to-face interactions imposed by the COVID-19 pandemic, alternative methods for data collection were required to facilitate anthropometric analysis. This study aimed to determine if there are differences in the measurement results of maxillary incisor displays when smiling through a profile photograph captured with a digital camera versus a webcam. This analytical observational study had a cross-sectional design and involved 110 participants who met the inclusion criteria. Profile photographs were captured with both a digital camera and a webcam. The maxillary incisor display was measured from both sets of profile photographs using CorelDraw Graphic Suite 2022 and was further analysed using the Chi-square test. The measurements of maxillary incisor display obtained from a digital camera and a webcam showed agreement in 67.3% of participants, whereas 32.7% were classified in different smile categories. Overall, the measurements obtained from two devices differed significantly (p = 0.003). Using a digital camera and webcam to take profile photos produced significantly different anthropometric measurements, suggesting that digital cameras should be preferred for standardized smile analysis.